Risk factors for poor outcome in diabetic keto acidosis at the initial presentation among children with type 1 diabetes mellitus - J., Merceline Alice PonJeba; Varadarajan, Poovazhagi (International Journal of Contemporary Pediatrics, 2018)
Background: Diabetic keto acidosis (DKA) is a serious metabolic disorder among children with new onset Type 1 Diabetes mellitus and is associated with high morbidity and mortality. Objective of the present study was to assess the risk factors associated with mortality in DKA at its initial presentation among children with new onset type 1 diabetes mellitus (T1DM). Methods: A case control study was designed and conducted in the Institute of child Health and Hospital for children, Madras Medical College, Chennai from February 2013 to February 2015. All children admitted with DKA as initial presentation of type 1 Diabetes mellitus were enrolled for this study. Results: Out of 72 new cases of T1DM, diagnosed during the study period 47 children had DKA and 25 children presented without DKA. Of the 47 children 6 children died. On comparing risk factors for mortality in DKA at the initial presentation, delayed treatment(p-0.002), altered sensorium at presentation(p-0.04), high urea(p-0.014) creatinine(p-0.042), lower bicarbonates (p-0.035), higher sodium(p-0.025) and lower pH(p-0.009) were found to be significantly associated with mortality. Overall mortality in DKA at its initial presentation is 12.8%. Conclusions: Delay in therapy for DKA and presence of features of severe disease at admission are significant risk factors for mortality.